A hypothesis on the enigmatic nature of psychosis. Issue 2 (2nd July 2020) - De Masi, Franco
ABSTRACT: This contribution deals with the difficulty in understanding the specific nature of psychotic functioning. These patients distort their perceptive apparatus to create dissociated sensorial worlds in which to live. They cannot be treated with the analytic technique employed with neurotic patients because they are unable to use the intuitive functions that enable psychic reality to be recognized. My hypothesis is that their mind functions as a sensory organ that is able to produce a new alternative reality to the real one. This paper develops a series of considerations on the nature of the enigma of psychosis and the way in which it is possible to analytically meet the psychotic patient.